Study of trends in digitalization of the world economy - Kobielieva, T. O.; Pererva, P. G.; Jakushko, A. E. (My University, 2023)
The opinions of experts who are representatives of large international research organizations are summarized, it seems possible to single out several primary trends that in the long term will have a significant impact on economic growth indicators: cloud computing; internet of things; artificial intelligence; robotics; blockchain. It is these trends that serve as the basis for the fourth industrial revolution.
Дослідження тенденцій цифровізації світової економіки
Keywords: digitalization; global economy; development trends; economic growth